Prolog Ewangelii Jana w tradycji liturgicznej Kościoła prawosławnego – ku przekładom na język staro-cerkiewno-słowiański. Prolegomena - Szmajda, Jarosław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The most important issues related to the Church Slavonic translation of the liturgical pericopes of the Good News of the Resurrection of Christ presented in this article indicate the appearance of a great number of variants unknown in the Slavic region. An attempt to translate them is to some extent an analysis of their theological content conducted by the translators and authors of particular manuscripts. In the seventeen verses of the Prologue of the Gospel of St. John, the development of the theological thought is apparent. This pericope begins with the creation of the world and concludes on a strong ecclesiological note. The most significant variants of the Church Slavonic translation of the liturgical pericopes for the Feast of the Resurrection of the Lord indicate and emphasise their essential theological content.